2011
DOI: 10.1002/btpr.720
|View full text |Cite|
|
Sign up to set email alerts
|

The enhancement of neural stem cell survival and growth by coculturing with expanded sertoli cells in vitro

Abstract: Sertoli cells (SCs) have been described as the "nurse cells" of testis to provide essential growth factors and to create a proper environment for the development of other cells (e.g., germinal and neural stem cell). However, the physiological functions of the SCs obtained from different culture conditions are different in a coculturing system, and thus the optimal SC culturing condition should be investigated in vitro. In this paper, primary Sertoli cells were isolated from a 12-day-old mouse and expanded in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In previous study, we reported that SCs can enhance the growth and survival of NSCs and neurons (33,34). In this study, a transwell coculture system was employed in order to determine the mechanism: whether the promotion of neurite outgrowth and prosurvival were mediated only by putative secreted factors or regulated by cell surface-anchored factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous study, we reported that SCs can enhance the growth and survival of NSCs and neurons (33,34). In this study, a transwell coculture system was employed in order to determine the mechanism: whether the promotion of neurite outgrowth and prosurvival were mediated only by putative secreted factors or regulated by cell surface-anchored factors.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, we reported that expanded SCs could effectively stimulate outgrowth of NSCs in a coculture system (33,34). In this study, we showed that SCs promoted the survival and neurite outgrowth of neurons without direct contact.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis of the numerical variables was performed using a two‐sample, two‐tailed t ‐test. A value of p < 0.05 is considered to be significant .…”
Section: Methodsmentioning
confidence: 99%
“…Although these signals can be presented to stem cells in vitro, such as by immobilization to materials, the large number of different signals and varying times for exposure may not allow for recapitulation of stem cell differentiation. In view of this, the presence of other cells in coculture with stem cells can be a useful tool to guide in vitro stem cell differentiation and lineage commitment. …”
Section: Lineage Commitment Induced By Coculturesmentioning
confidence: 99%